Systems and methods for simultaneously forming and improving anti-reflection and anti-glare behavior of glass articles
Through heat treatment and thermoforming, the cladding layer of the glass laminate is separated, and combined with etching treatment, the problems of high cost and difficult to control of traditional AR coatings and AG processing are solved, and improved anti-reflection and anti-glare performance are achieved. Reduced production costs.
Patent Information
- Application Number
- CN202380052120.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-06-02
- Publication Date
- 2025-02-21
AI Technical Summary
Traditional anti-reflective (AR) coatings and anti-glare (AG) treatment processes are costly and difficult to control, and AR coatings and AG characteristics are difficult to optimize simultaneously.
By preheating the substrate including the core layer and the cladding layer, heat treatment and thermoforming are performed, the cladding layer is separated and deformed, forming a molded glass laminate, and etching is performed to optimize optical performance.
The anti-reflection and anti-glare properties of glass products are achieved simultaneously, reducing production costs, and showing high transmittance and low reflectivity in the visible to infrared wavelength range.
Smart Images

Figure CN119497703A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority under 35 USC §119 to U.S. Provisional Application No. 63 / 350,485, filed on June 9, 2022, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present disclosure relates to anti-reflective (AR) and anti-glare (AG) glass laminates having improved optical properties and methods of making the same. Background Art
[0004] Conventional anti-reflection (AR) coatings consist of a single or multi-layer stack of low- and high-refractive-index materials that destructively interfere with the different reflections of the stack. Currently, AR coatings with satisfactory anti-reflection quality in the visible wavelength range or beyond require multiple different coatings. Anti-glare (AG) treatments work by scattering incident light away from the specular direction. This is usually achieved by patterning the surface with etching, texture coatings, or bulk scatterers. However, such AR coating and AG treatment processes significantly increase the cost of the base glass product. Summary of the invention
[0005] In view of the above, an object of the present disclosure is to provide an apparatus and method for simultaneously thermally forming and improving the AR and AG behaviors of a glass article.
[0006] An exemplary embodiment of the present disclosure provides a method for forming a shaped glass laminate, which includes preheating a substrate including a core layer and at least one cladding layer, the at least one cladding layer comprising a phase-separable glass composition, and simultaneously heat treating and hot forming the substrate so that the at least one cladding layer is phase-separated and at least a portion of the substrate is deformed to form the shaped glass laminate, the simultaneous heat treating and hot forming of the substrate including heating the substrate and simultaneously pressing the substrate, and etching the substrate.
[0007] In some embodiments, the step of simultaneously heat treating and thermoforming the substrate further comprises cooling the substrate. In some embodiments, the step of preheating the substrate comprises heating the substrate to a temperature below the glass transition temperature of the at least one cladding layer. In some embodiments, the step of preheating the substrate comprises heating the substrate using multiple preheating stages, each preheating stage comprising a preheating temperature range and a preheating hold time. In some embodiments, the step of simultaneously heat treating and thermoforming the substrate comprises: heating the substrate to a temperature ranging from the glass transition temperature of the at least one cladding layer to the softening point of the at least one cladding layer; and applying a pressure of at least 0.9 MPa to the substrate.
[0008] In some embodiments, the step of simultaneously heat treating and thermoforming the substrate comprises simultaneously heating the substrate to about 750°C and applying a pressure of about 0.9 MPa to the substrate for at least 600 seconds. In some embodiments, the step of simultaneously heat treating and thermoforming the substrate comprises simultaneously heating the substrate at about 750°C and applying a pressure of about 0.9 MPa to the substrate on a forming surface for at least 1200 seconds. In some embodiments, the step of simultaneously heat treating and thermoforming the substrate comprises simultaneously heating the substrate at a temperature greater than or equal to about 710°C and contacting the substrate with a forming surface at a pressure in the range of 0.1 MPa to 0.9 MPa. In some embodiments, the step of simultaneously heat treating and thermoforming the substrate comprises simultaneously heating the substrate to a temperature at which spinodal phase separation occurs in at least one coating layer and contacting the substrate with a forming surface at a pressure at which deformation of the substrate occurs.
[0009] The method of claim 10, wherein the shaped surface comprises a pre-shaped mold. In some embodiments, the step of cooling the substrate comprises cooling the substrate using a plurality of cooling stages, each cooling stage comprising a cooling temperature range, a pressure, and a cooling hold time. In some embodiments, the step of etching the substrate comprises applying at least a 2% by volume hydrogen fluoride (HF) solution to the substrate for at least 90 seconds; immersing the substrate in a dihydrogen monoxide (H2O) bath for at least 120 seconds; rinsing the substrate in deionized water; and cleaning the substrate with nitrogen (N2).
[0010] Another exemplary embodiment of the present disclosure provides a method for forming a phase-separated glass laminate with improved anti-reflection (AR) and anti-glare (AG) properties, the method comprising providing a substrate comprising a core layer and at least one cladding layer fused to the core layer, simultaneously heat treating and forming the substrate using a hot press, heating the substrate to a temperature at which spinodal phase separation occurs in the at least one cladding layer, pressing the substrate onto a forming surface, and etching the substrate.
[0011] In some embodiments, the step of heating the substrate to a temperature at which the at least one coating undergoes spinodal phase separation comprises heating the substrate to a temperature ranging from the glass transition temperature of the at least one coating to the softening point of the at least one coating for at least 1200 seconds. In some embodiments, the step of pressing the substrate onto the forming surface comprises arranging the substrate on a preforming mold, and applying a first pressure of at least 0.9 MPa to the substrate for at least 1200 seconds. In some embodiments, the method further comprises reducing the first pressure applied to the substrate from 0.9 MPa to a second pressure in the range of 0.1 MPa to 0.4 MPa. In some embodiments, prior to the steps of simultaneously heat treating and forming the substrate, the method further comprises preheating the substrate to a temperature below the glass transition temperature of the at least one coating.
[0012] Another exemplary embodiment of the present disclosure provides a method for forming and molding a phase-separated glass laminate with improved anti-reflection (AR) and anti-glare (AG) properties, which includes providing a substrate including a core layer and at least one cladding layer, simultaneously heat treating and forming the substrate using a hot press, by preheating the substrate to a first temperature, heating the substrate to a second temperature higher than the first temperature, at which temperature the at least one cladding layer undergoes spinodal phase separation, and pressing the substrate into a forming surface under a first pressure to permanently deform the substrate; and cooling the substrate to a third temperature lower than the second temperature, while pressing the substrate into the forming surface under a second pressure less than the first pressure, and etching the substrate.
[0013] In some embodiments, the step of simultaneously heat treating and forming the substrate further comprises cooling the substrate to a fourth temperature lower than the third temperature while pressing the substrate into the forming surface at a third pressure less than the second pressure. In some embodiments, the second temperature is in the range of 710° C. to 750° C., and the first pressure is greater than 0.4 MPa.
[0014] Another exemplary embodiment of the present disclosure provides a shaped glass laminate article, comprising: a core layer, at least one cladding layer fused to the core layer, the at least one cladding layer including a porous region on its outer surface, the core layer and the at least one cladding layer being deformed to form the shaped glass laminate, wherein the shaped glass laminate article has a transmittance greater than 98% over the entire spectral range from about 400 nm to about 2200 nm, and for one surface of the shaped glass laminate article, the shaped glass laminate article has a reflectance less than 1% over the entire spectral range from about 400 nm to 2200 nm. In some embodiments, the thickness of the porous region has a percentage deviation of less than 12%.
[0015] In some embodiments, the porous region has an average pore size greater than or equal to 10 nm and less than or equal to 200 nm. In some embodiments, the porous region has an average pore size greater than or equal to 20 nm and less than or equal to 150 nm. In some embodiments, the porous region has a porosity greater than or equal to 0.16 and less than or equal to 0.22. In some embodiments, the thickness of the porous region is greater than or equal to 350 nm and less than or equal to 450 nm. In some embodiments, the thickness of the porous region is greater than or equal to 375 nm and less than or equal to 400 nm.
[0016] Another exemplary embodiment of the present disclosure provides a shaped glass laminate product, comprising a core layer, at least one cladding layer fused to the core layer, the at least one cladding layer comprising a porous area on an outer surface thereof, the core layer and the at least one cladding layer being deformed to form the shaped glass laminate, wherein the shaped glass laminate product has a transmittance greater than or equal to 97% over the entire spectral range from about 400 nm to about 2200 nm, and the shaped glass laminate product has a reflectance less than or equal to 3% at the outer surface over the entire spectral range from about 400 nm to 2200 nm.
[0017] In some embodiments, the shaped glass laminate article has a transmittance greater than 98% over the entire visible spectrum from about 400 nm to about 2200 nm. In some embodiments, the shaped glass laminate article has a reflectance less than 1% over the entire visible spectrum from about 400 nm to about 2200 nm. In some embodiments, the porous region has an average pore size greater than or equal to 10 nm and less than or equal to 200 nm. In some embodiments, the porous region has a porosity greater than or equal to 0.16 and less than or equal to 0.22. In some embodiments, the thickness of the porous region is greater than or equal to 350 nm and less than or equal to 450 nm. In some embodiments, the thickness of the porous region has a percentage deviation of less than 12%.
[0018] The following will describe the embodiments of the present disclosure, but it should be understood that the present disclosure is not limited to the described embodiments and that various modifications can be made to the present disclosure without departing from the basic principles. Therefore, the scope of the present disclosure will only be determined by the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Various embodiments are disclosed, by way of example only, with reference to the following schematic drawings wherein corresponding reference characters indicate corresponding parts.
[0020] Figure 1 is a cross-sectional view of an exemplary glass article.
[0021] Figure 2 is a cross-sectional view of an exemplary overflow distributor that can be used to form an exemplary glass article.
[0022] Figure 3 An exemplary melt-drawn laminated glass processing process is shown.
[0023] Figure 4A is a top view of an exemplary preform before forming.
[0024] Figure 4B yes Figure 4A A top view of an exemplary preform shown in FIG. 1 after forming.
[0025] Figure 4C It is roughly along Figure 4B A cross-sectional view of an exemplary preform taken along line 4C-4C in FIG.
[0026] Figure 5 A graph illustrating an exemplary embodiment of a method of making an exemplary glass article is shown.
[0027] Figure 6 Shows the Figure 5 A graph of the data displayed in the graph.
[0028] Figure 7 Graphs illustrating the transmittance at different wavelengths of glass articles formed by various methods are shown.
[0029] Figure 8 Graphs illustrating the reflectivity at different wavelengths of glass articles formed by various methods are shown.
[0030] Fig. 9 It is a perspective view of glass products.
[0031] Fig.10 Show description Fig. 9 The graph of reflectivity at different wavelengths at different locations around the glass product shown.
[0032] Fig.11 Shows Fig. 9 Images of the microstructure at different locations around the glass object shown.
[0033] Fig.12 Show description Fig. 9 Warp measurement surface mapping of the glass article shown. DETAILED DESCRIPTION
[0034] First, it should be understood that like reference numerals in different drawings identify like or functionally similar structural elements.It should be understood that the claims are not limited to the disclosed aspects.
[0035] Furthermore, it is to be understood that the present disclosure is not limited to the particular methods, materials and adjustments described, as such may, of course, vary. It is also to be understood that the terminology used herein is for the purpose of describing particular aspects only, and is not intended to limit the scope of the claims.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by one of ordinary skill in the art to which the present disclosure relates. It should be understood that any methods, devices or materials similar or equivalent to those described herein may be used in the practice or testing of the exemplary embodiments.
[0037] It should be understood that the term "substantially" is synonymous with terms such as "almost", "very close", "about", "approximately", "about", "adjacent", "near", "essentially", "substantially close", "nearby", and the like, and these terms can be used interchangeably as shown in the specification and claims. It should be understood that the term "adjacent" is synonymous with terms such as "near", "close", "adjacent", "adjacent", "immediately adjacent", "adjacent", and the like, and these terms can be used interchangeably as shown in the specification and claims. The term "approximately" means a value within 10% of the specified value. The term "approximately" and its synonyms refer to quantities, sizes, formulas, parameters and other quantities and features are not and need not be exact, but can be approximate and / or larger or smaller as needed, reflecting tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those skilled in the art. When the term "about" is used to describe a value or endpoint of a range, the disclosure should be understood to include the specific value or endpoint referred to. Regardless of whether the value or endpoint of a range in the specification states "about", the value or endpoint of the range is intended to include two modes: one is modified by "about" and one is not modified by "about". It can be further understood that the endpoint of each range is significant relative to the other endpoint and independent of the other endpoint.
[0038] It should be understood that, unless otherwise stated, the use of "or" in this application refers to a "non-exclusive" configuration. For example, when it is said that "item x is A or B", it should be understood that it may mean one of the following: (1) item x is only one or the other of A and B; (2) item x is both A and B. In other words, the word "or" is not used to define an "exclusive or" arrangement. For example, the "exclusive or" configuration of "item x is A or B" requires that x can only be one of A and B. In addition, as used herein, "and / or" is intended to represent a grammatical conjunction used to indicate that one or more of the listed elements or conditions may be included or appear. For example, a device that includes a first element, a second element, and / or a third element is intended to be interpreted as any of the following structural configurations: a device that includes the first element; a device that includes the second element; a device that includes the third element; a device that includes the first element and the second element; a device that includes the first element and the third element; a device that includes the first element, the second element, and the third element; or, a device that includes the second element and the third element.
[0039] In addition, as used herein, the phrase "comprising at least one of the following" or "including at least one of the following" in conjunction with a system or element means that the system or element includes one or more of the elements listed after the phrase. For example, a device comprising at least one of the following: a first element; a second element; and, a third element, is intended to be interpreted as any of the following structural configurations: a device comprising the first element; a device comprising the second element; a device comprising the third element; a device comprising the first element and the second element; a device comprising the first element and the third element; a device comprising the first element, the second element, and the third element; or, a device comprising the second element and the third element. A similar interpretation applies to the phrase "for at least one of the following" as used herein.
[0040] Transmittance percentage (%) is defined as the percentage of incident light that passes through the thickness of a material. Reflectance percentage (%) is defined as the percentage of incident light that is reflected from an interface when light travels from one medium to another (e.g., from air to glass). Transmittance % and reflectance % may also be defined for multiple interface systems, including discontinuous and gradient interfaces. As used herein, reflectance % refers to the reflectance of a surface unless otherwise specified.
[0041] Distinction of image (DOI) is a quantification of the deviation of the direction of light propagation from the regular direction due to scattering during transmission or reflection.
[0042] Gloss is defined as a measure proportional to the amount of light reflected from a surface and is used to determine how shiny a surface is. Haze causes a reduction in reflective contrast and can cause halos around light sources; these undesirable effects can significantly reduce visual quality.
[0043] Phase separation is defined as the separation of a homogeneous medium into two or more different homogeneous materials, usually with different chemical properties.
[0044] Define the glass refractive index as the refractive index of the material.
[0045] The coefficient of thermal expansion (CTE) is defined as the average coefficient of thermal expansion of the glass composition over the temperature range from about 20°C to about 300°C.
[0046] References to element positions herein (e.g., "top," "bottom," "upper," "lower," etc.) are only used to describe the orientation of the various elements in the figures. It should be noted that the orientation of the various elements may be different according to other exemplary embodiments, and such variations are intended to be encompassed by the present disclosure.
[0047] The specific and preferred values and ranges disclosed for components, ingredients, additives, dimensions, conditions, time, etc. are for illustration only; they do not exclude other defined values or other values within the defined ranges. The compositions, articles and methods of the present disclosure may include any value described herein, or any combination of values, specific values, more specific values and preferred values, including explicit or implicit intermediate values and ranges.
[0048] Conventional techniques for reducing reflections from glass surfaces include the use of AR coatings and AR texturing. However, both conventional AR and AG techniques (A) are limited by cost and time (e.g., AR coatings typically require multiple coatings of different compositions); (B) can be difficult to control; and (C) are challenging to jointly optimize (i.e., AR coatings and AG properties can counteract each other's effects).
[0049] In the present disclosure, a new method of using a laminated glass cladding as an AR / AG surface is described. To achieve this, a multi-step process is used, with an initial step including preheating the glass article, followed by simultaneous thermoforming and phase separation chemical treatment of the cladding layer, and etching. An embodiment provides a cycle of heat treatment and surface etching of the glass article, which can form a gradient refractive index type material with improved optical properties (e.g., a total reflectivity of less than 1% on the surface, a total transmittance greater than 98%, lower gloss, and lower DOI) for various uses, such as display applications (e.g., automotive interiors, laptop housings, smart watches, etc.). The resulting glass laminate structure provided by the embodiment is stronger than a single glass system. In some embodiments, at least one of the cladding layer and the core layer or a combination thereof can be phase separated at different grain sizes to optimize the cover glass design for a specific application.
[0050] Exemplary embodiments of the present disclosure provide a method for simultaneously phase-separating and three-dimensionally forming a glass product. In some embodiments, the simultaneous phase separation and three-dimensional (3D) heat-forming of the glass product is performed in a molding press operating at high temperature, wherein the glass product is pressed and formed while being heat-treated. In a subsequent step, once the glass product is formed and phase-separated, the glass product is subjected to an etching process.
[0051] Some advantages of the present disclosure include: 1) reducing production costs by performing some processes simultaneously; 2) achieving uniform surface treatment throughout the glass article without major adjustments to equipment or process steps; and, 3) obtaining glass articles having an average transmittance (Tx) greater than 98% and a reflectance (Rx) less than 1% on both surfaces of the article at wavelengths from visible light to infrared (IR) (approximately 400-2200 nm).
[0052] Now referring to the accompanying drawings, Figure 11 is a cross-sectional view of a glass article or sheet or substrate 100. In some embodiments, the glass sheet 100 comprises a laminate comprising a plurality of glass layers. The laminate may be as follows: Figure 1 The glass sheet 100 includes a core layer 102 disposed between a cladding layer 104 and a cladding layer 106. In some embodiments, as shown Figure 1 As shown in FIG. 1 , cladding layer 104 and cladding layer 106 are outer layers.
[0053] The core layer 102 includes a first major surface 108 and a second major surface 110 opposite the first major surface. In some embodiments, the cladding layer 104 is fused to the first major surface 108 of the core layer 102. Additionally or alternatively, the cladding layer 106 is fused to the second major surface 110 of the core layer 102. In such embodiments, the interface between the cladding layer 104 and the core layer 102 and / or between the cladding layer 106 and the core layer 102 is free of any bonding material, such as, for example, an adhesive, a coating, or any non-glass material added or configured to adhere the respective cladding layer to the core layer. Thus, the cladding layer 104 and / or the cladding layer 106 are directly fused to the core layer 102 or directly adjacent to the core layer 102. In some embodiments, the glass sheet 100 includes one or more intermediate layers disposed between the core layer 102 and the cladding layer 104 and / or between the core layer 102 and the cladding layer 106. For example, the intermediate layer includes an intermediate glass layer and / or a diffusion layer formed at the interface of the core layer and the cladding layer. The diffusion layer can include a mixed zone including components of the layers adjacent to the diffusion layer.In some embodiments, glass sheet 100 includes a glass-glass laminate (eg, an in-situ fused multilayer glass-glass laminate) wherein the interface between immediately adjacent glass layers is a glass-glass interface.
[0054] In some embodiments, a first layer (e.g., core layer 102) comprises a first glass composition and a second layer (e.g., cladding layer 104 and / or cladding layer 106) comprises a second glass composition that is different from the first glass composition. Figure 1 In the embodiment shown in , the core layer 102 comprises a first glass composition, and each of the cladding layer 104 and the cladding layer 106 comprises a second glass composition. In other embodiments, the first cladding layer comprises the second glass composition, and the second cladding layer comprises a third glass composition different from the first glass composition and / or the second glass composition.
[0055] The glass sheet may be formed using a suitable process, such as, for example, a melt-draw, a down-draw, a slot-draw, an up-draw, or a float process. The layers of the glass sheet may be laminated during the forming of the glass sheet, or may be formed separately and then laminated to form the glass sheet. In some embodiments, the glass sheet is formed using a melt-draw process.
[0056] Figure 2 2 is a cross-sectional view of an exemplary embodiment of an overflow distributor 200 that can be used to form a glass sheet (such as, for example, glass sheet 100). Overflow distributor 200 can be configured in a manner as described in U.S. Patent No. 4,214,886 (Corning Incorporated), the entire contents of which are incorporated herein by reference. For example, overflow distributor 200 includes a lower overflow distributor 220 and an upper overflow distributor 240 located above the lower overflow distributor. Lower overflow distributor 220 includes groove 222. A first glass composition 224 is melted and fed into groove 222 in a viscous state. The first glass composition 224 forms the core layer 102 of glass sheet 100, as further described below. Upper overflow distributor 240 includes groove 242. A second glass composition 244 is melted and fed into groove 242 in a viscous state. The second glass composition 244 forms the first cladding layer 104 and the second cladding layer 106 of glass sheet 100, as further described below.
[0057] The first glass composition 224 overflows the groove 222 and flows downward along the opposite outer forming surfaces 226 and 228 of the underflow distributor 220. The outer forming surfaces 226 and 228 converge at the draw line 230. The divided flows of the first glass composition 224 flowing down along the respective outer forming surfaces 226 and 228 of the underflow distributor 220 converge at the draw line 230, where they merge together to form the core layer 102 of the glass sheet 100.
[0058] The second glass composition 244 overflows the groove 242 and flows downward along the opposite outer forming surfaces 246 and 248 of the upper overflow distributor 240. The second glass composition 244 is deflected outward by the upper overflow distributor 240 so that the second glass composition flows around the lower overflow distributor 220 and contacts the first glass composition 224 flowing through the outer forming surfaces 226 and 228 of the lower overflow distributor. The split flows of the second glass composition 244 merge with the corresponding split flows of the first glass composition 224 flowing down along the corresponding outer forming surfaces 226 and 228 of the lower overflow distributor 220. When the flows of the first glass composition 224 converge at the draw line 230, the second glass composition 244 forms the first cladding layer 104 and the second cladding layer 106 of the glass sheet 100.
[0059] In some embodiments, the first glass composition 224 of the core layer 102 in a viscous state is contacted with the second glass composition 244 of the first cladding layer 104 and the second cladding layer 106 in a viscous state to form a laminate. In some such embodiments, the laminate is a portion of the draw line 230 of the glass ribbon traveling away from the underflow distributor 220, such as Figure 2As shown in . The glass ribbon can be drawn from the underflow distributor 220 by a suitable method, such as gravity and / or pulling rollers. The glass ribbon cools as it travels away from the underflow distributor 220. The glass ribbon is cut to separate the laminated sheets therefrom. In this way, the laminated sheets are cut from the glass ribbon. The glass ribbon can be cut using a suitable technique, such as, for example, scoring, bending, thermal shock and / or laser cutting. In some embodiments, the glass sheet 100 includes laminated sheets, such as Figure 1 The laminate is further processed (eg, by cutting or molding) to shape and process the glass sheet 100, as will be described in more detail below.
[0060] although Figure 1 The glass sheet 100 shown in the figure includes three layers, but other embodiments are also included in the present disclosure. In other embodiments, the glass sheet can have a determined number of layers, such as two layers, four layers or more layers. For example, a glass sheet including two layers can be formed using two overflow distributors, which are positioned so that the two layers are joined together when traveling away from the corresponding pull-out lines of the overflow distributors, or a single overflow distributor with a separation groove is used so that the two glass compositions flow through the relative outer forming surfaces of the overflow distributor and converge on the pull-out line of the overflow distributor. Additional overflow distributors and / or overflow distributors with separation grooves can be used to form a glass sheet including four or more layers. Therefore, by adjusting the overflow distributor accordingly, a glass sheet with a determined number of layers can be formed.
[0061] The first and second coating layers can be any composition that phase separates in a spinodal manner to produce a porous matrix. For example, the first and second coating layers can be formed by a composition comprising: silicon dioxide (SiO2) with a concentration ranging from 45wt% to 75wt% (e.g., ~60wt%), aluminum oxide (Al2O3) with a concentration ranging from 8wt% to 19wt% (e.g., ~12wt%), boron trioxide (B2O3) with a concentration ranging from 5wt% to 23wt% (e.g., ~18wt%), alkali metal oxides (e.g., LEO, Na2O, K2O, Rb2O, etc.) with a concentration ranging from 3wt% to 21wt% and alkaline earth metal oxides (e.g., MgO (~1-5wt%), CaO (-1-10wt%), SrO (-1-5wt%), etc.) with a concentration ranging from 1wt% to 15wt%. The cladding layer may be substantially free of arsenic (As) and cadmium (Cd) such that the degradation rate of the cladding layer is at least ten times the degradation rate of the core layer. In some examples, the cladding layer may be aluminosilicate glass with a high B2O3 content.
[0062] In some embodiments, the coating layers 104 and 106 are formed of a composition comprising 64.64 wt% SiO2, 7.38 wt% Al2O3, 16.45 wt% B2O3, 8.14 wt% CaO, 2.21 wt% MgO, 1.11 wt% SrO, and 0.07 wt% SnO2. In some embodiments, at least one of the coating layers 104 and 106 comprises 14-15% boron.
[0063] The core layer can be made of alkaline earth boroaluminosilicate glass (e.g., CORNING EAGLE Glass), FOTOFORM glass, CORNING IRIS TM GLASS OR CORNING The core layer may be formed of at least one of the following glasses. For example, the core layer may be formed of a glass having the following components: 79.3wt% SiO2, 1.6wt% Na2O, 3.3wt% K2O, 0.9wt% KNO3, 4.2wt% Al2O3, 1.0wt% ZnO, 0.0012wt% Au, 0.115wt% Ag, 0.015wt% CeCE, 0.4wt% Sb2O3, and 9.4wt% LEO. In some instances, the core layer may be formed of a glass composition falling within the range of the first and second cladding layers as described above. For example, the core layer may be formed of a glass having the following components: 56.57wt% SiO2, 16.75wt% Al2O3, 10.27wt% B2O3, 4.54wt% CaO, 3.18wt% K2O, 3.79wt% MgO, and 4.74wt% SrO. In some embodiments, for example, due to its ultra-low autofluorescence, the core layer includes CORNINGEAGLE GLASS OR CORNING IRIS TM The core layer provides structural strength to the cladding layer through a stress concentrator at the interface of the core layer and / or the cladding layer.
[0064] In some embodiments, the core layer 102 is formed of a composition including 62.4 wt% SiO2, 10.89 wt% Al2O3, 9.78 wt% B2O3, 5.37 wt% CaO, 2.24 wt% K2O, 6.23 wt% MgO, 3.03 wt% SrO, and 0.07 wt% SnO2. In some embodiments, the core layer 102 accounts for at least 90% of the glass sheet 100.
[0065] In some examples, the core layer may be formed of a glass composition having a relative humidity of greater than or equal to about 40×10 -7 In some examples, the average CTE of the core glass composition may be greater than or equal to about 60×10 -7 In some examples, the average CTE of the core glass composition may be greater than or equal to about 80×10 -7 / °C. In some examples, the first and second cladding layers have an average CTE different from the average CTE of the core layer. In some examples, the first and second cladding layers have an average CTE lower than the average CTE of the core layer. In some examples, the first and second cladding layers have an average CTE higher than the average CTE of the core layer. In some embodiments described herein, the glass cladding layer is formed of a cladding glass composition having a CTE less than or equal to about 40×10 -7 In some embodiments, the average CTE of the coating glass composition may be less than or equal to about 37×10 -7 In yet other embodiments, the average CTE of the coating glass composition may be less than or equal to about 35×10 -7 / ℃.
[0066] In some embodiments, the glass compositions of the core layer 102 and the cladding layers 104 and 106 include substantially similar softening points. For example, it is desirable that the thermoforming temperature and the phase separation temperature are similar (e.g., about 750° C.). This reduces the overall time required for a single thermoforming and phase separation step to occur. In some embodiments, the glass composition of the core layer 102 includes a lower softening point than the glass composition of the cladding layers 104 and 106. Such different softening points enable the glass sheet 100 to be formed into a shaped glass article while avoiding potentially harmful surface interactions between the glass sheet and the forming surface, as described herein.
[0067] Figure 3 The fusion-drawn laminated glass processing process is shown. The change in the slope of the glass refractive index indicates that there is a gradient refractive index effect on the surface, which helps to minimize Fresnel reflections on the surface. The initial fusion-drawn glass laminate is equivalent to the above Figure 1The glass article 100 described in the embodiment of the present invention has at least one amorphous cladding layer (cladding layer 104 and / or 106) and an amorphous core layer 102. In the first step, the glass article 100 undergoes a series of heat treatments, in which the glass article is heated at a specific temperature for a specified period of time. In the second step, the glass article 100 is simultaneously heat treated and thermoformed to transform the glass article 100 into a 3D formed glass article 110 including phase-separated cladding layers 114 and 116. It should be understood that an embodiment of the second step including simultaneous heating and thermoforming may include heat treatment and application of pressure at multiple levels for multiple time periods. In the third step, the glass article 110 is etched and transformed into a glass article 120 including cladding layers 124 and 126. The applied etching treatment removes one of the two phases of the cladding layers 114 and 116, leaving porous cladding layers 124 and 126.
[0068] Step 1 - Preheating
[0069] The preheating step may be performed in a high temperature forming press or furnace, which is operable to maintain and heat the glass article. In this step, the glass article is passed through one or more temperature levels for a predetermined period of time so that the temperature of the glass article is raised to a temperature relatively close to and below the phase separation temperature of the glass article.
[0070] Step 2 - Simultaneous heat treatment and hot forming
[0071] The heat treatment and forming steps are performed in a high temperature forming press. In some embodiments, the press comprises nine zones and operates in an inert atmosphere and uses a preformed graphite die. Figure 4A The preform 300 is shown prior to forming (ie, prior to heat treatment and forming steps). Figure 4B -C shows the preform 300 after forming, where heat treatment and forming steps are used to form / shape the preform 300 into a 3D shape. In some embodiments, the press includes one or more of the following specifications: 1) 1°C temperature control; 2) maximum mold size 120×180×25-50mm; 3) maximum forming temperature 850°C; 4) positive pressure range 0.001-0.9MPa; and 5) the ability to heat, press and cool sequentially.
[0072] In some embodiments, the simultaneous heat treatment and thermoforming steps include the following method, each zone has a set temperature and time spent per sample, as well as the pressure applied. The first four zones in the press are dedicated to heating the glass article 100 and are used to heat the glass article 100 to a phase separation temperature (e.g., 750° C.). The last three zones are used for thermoforming, where pressure is applied to the glass article to form it and simultaneously phase separate the glass article 100, particularly the cladding layers 104 and 106. In some embodiments, the glass article 100 is heated to a temperature greater than or equal to the glass transition temperature T of the cladding layers 104 and / or 106. g Temperature. Glass transition temperature T g The temperature at which glass changes from an elastic material to a viscoelastic material with respect to increasing temperature, characterized by the onset of a rapid change in thermal expansion, as is known in the art. In some embodiments, the glass article 100 is heated to a temperature greater than or equal to the glass transition temperature T of the cladding layers 104 and 106. g and less than or equal to the softening point T of the coating layers 104 and 106 s (e.g., 500-1000 degrees Celsius). The softening point of the glass or the Littleton softening point T s , is the temperature at which glass moves under its own weight, as is known in the art. In an embodiment, the softening point is determined according to the ASTM C338-93 (2019) Standard Test Method for Softening Point of Glass. In some embodiments, the glass article 100 is heated to a temperature at which the coating layers 104 and 106 are spinodally phase separated. In some embodiments, the glass article 100 takes a total of 20 minutes at 750°C. Subsequent zones (e.g., two zones) are used to cool the glass article and reduce the forming pressure. Therefore, in the same step, the glass article 100 is transformed into a glass article 110, which includes phase-separated coating layers 114 and 116 and a 3D shape. In some embodiments, the total processing time for performing the phase separation and 3D forming steps simultaneously is about 30 minutes.
[0073] Figure 5-6 An exemplary implementation of steps 1-2 of the present disclosure is shown in FIG. Figure 5 A graph 400 showing the process of steps 1-2 is shown, where line 402 represents the temperature of the press and line 404 represents the pressure of the press. Figure 6 Shows the Figure 5 410 of the data related to the curve graph shown in FIG. Steps 1-2 of the present disclosure can be decomposed into the following nine steps or zones. It should be understood that the embodiments of the present disclosure provide Figure 6 The time periods set in represent minimum time periods, and embodiments include longer time periods for each zone or step to still obtain the final target glass product.
[0074] In the first zone or step, the press applies a temperature of 400°C to the glass article 100 for 90 seconds. In the first zone, no pressure is applied to the glass article 100. In some embodiments, in the first zone, the glass article 100 is heated to 400°C.
[0075] In the second zone or step, the press applies a temperature of 500°C to the glass article 100 for 90 seconds. In the second zone, no pressure is applied to the glass article 100. In some embodiments, in the second zone, the glass article 100 is heated to 500°C.
[0076] In the third zone or step, the press applies a temperature of 600°C to the glass article 100 for 90 seconds. In the third zone, no pressure is applied to the glass article 100. In some embodiments, in the third zone, the glass article 100 is heated to 600°C.
[0077] In the fourth zone or step, the press applies a temperature of 700°C to the glass article 100 for 90 seconds. In the fourth zone, no pressure is applied to the glass article 100. In some embodiments, in the fourth zone, the glass article 100 is heated to 700°C.
[0078] In the fifth zone or step, the press applies a temperature of 750° C. and a pressure of 0.9 MPa to the glass article 100 for 600 seconds. In some embodiments, in the fifth zone, the glass article 100 is heated to 750° C. It should be understood that the press applies pressure to the glass article 100 so that it engages with the preform mold (e.g., mold 300) to form the glass article 100. In addition, in some embodiments, the coating layers 104 and 106 begin to phase separate at about 710° C. It should be understood that embodiments include achieving heat transfer through contact between the press and the glass article 100 (i.e., zones 5-7) during the heating process of the press.
[0079] In the sixth zone or step, the press applies a temperature of 750° C. and a pressure of 0.9 MPa to the glass article 100 for 600 seconds. In some embodiments, in the sixth zone, the glass article 100 is heated to 750° C. In some embodiments, the fifth and sixth zones are combined so that the press applies a temperature of 750° C. and a pressure of 0.9 MPa to the glass article 100 for 1200 seconds.
[0080] In the seventh zone or step, the press applies a temperature of 692°C and a pressure of 0.4 MPa to the glass article 100 for 90 seconds. In some embodiments, in the seventh zone, the glass article 100 is cooled to 692°C.
[0081] In the eighth zone or step, the press applies a temperature of 633°C and a pressure of 0.1 MPa to the glass article 100 for 90 seconds. In some embodiments, in the eighth zone, the glass article 100 is cooled to 633°C.
[0082] In the ninth zone or step, the press applies a temperature of 450° C. to the glass article 100 for 90 seconds. In the ninth zone, no pressure is applied to the glass article 100. In some embodiments, in the eighth zone, the glass article 100 is cooled to 633° C. During testing of the disclosed method, it was found that zones 7-9 stop the phase separation process (i.e., take the coating out of the phase separation state) and set the shape of the glass article. This is due to gradual cooling and pressure release.
[0083] After the ninth zone, the glass article 100 is said to have been transformed into a formed and phase separated glass article 110. The glass article 110 may then proceed to an etching process step in which the phase separated cladding layers 114 and 116 and the core layer 102 are liquid or vapor etched.
[0084] Embodiments of the present disclosure provide that during steps 5-7, the glass article, particularly the coating layers 104 and 106, undergo spinodal phase separation at the nanometer level. Such spinodal phase separation transforms the single-phase coating layers 104 and 106 into two-phase coating layers 114 and 116. This allows an etching process (described below) to erode away one of the two phases so that the coating layers 114 and 116 are porous and exhibit better AG and / or AR properties. While the spinodal phase is separating, the glass article 100 is hot formed and formed into a desired shape.
[0085] Step 3 - Etching
[0086] In some embodiments, the etching process can be performed as follows. A 2 volume percent (2 vol%) hydrogen fluoride (HF) solution is prepared. One side of the glass article 110 is taped for single-side etching. The glass article 110 is etched in a certain volume of HF solution for a period of time, for example, 90 seconds. Then, the glass article 110 is immersed in a H2O bath for a period of time, for example, 120 seconds. Then, the glass article 110 is rinsed in deionized (DI) water and dried and cleaned using N2. After undergoing this etching process, the glass article 110 is said to have been transformed into a glass article 120, wherein the etching process removes one of the two phases of the coating layers 114 and 116, leaving a single-phase porous coating layer 124 and 126.
[0087] In some embodiments, wet chemical etching is performed using a suitable component capable of degrading or dissolving the glass article. For example, suitable wet etching chemicals include acids (e.g., HCl, HNO3, H2SO4, H3PO4, H3BO3, HBr, HClO4, HF, acetic acid, citric acid, NH4F, ammonium difluorate), bases (e.g., LiOH, NaOH, KOH, RbOH, CsOH, Ca(OH)2, Sr(OH)2, Ba(OH)2), H2O, or a combination thereof. In some examples, the wet chemical etchant has a concentration ranging from 0.1 vol% to 10 vol%, or 0.2 vol% to 9 vol%, or 0.3 vol% to 8 vol%, or 0.4 vol% to 7 vol%, or 0.5 vol% to 6 vol%, or 0.6 vol% to 5 vol%, or 0.25 vol% to 5 vol%, or 0.25 vol% to 3 vol%, or 0.25 vol% to 2 vol%, or any intermediate value or range disclosed therein.
[0088] In some embodiments, the wet chemical etchant has 0.1 vol%, or 0.15 vol%, or 0.2 vol%, or 0.25 vol%, or 0.3 vol%, or 0.35 vol%, or 0.4 vol%, or 0.45 vol%, or 0.5 vol%, or 0.55 vol%, or 0.6 vol%, or 0.65 vol%, or 0.7 vol%, or 0.75 vol%, or 0.8 vol%, or 0.85 vol%, or 0.9 vol%, or 0.95 vol%, or 1 vol%, or 1. 1vol%, or 1.2vol%, or 1.3vol%, or 1.4vol%, or 1.5vol%, or 1.6vol%, or 1.7vol%, or 1.8vol%, or 1.9vol%, or 2vol%, or 2.25vol%, or 2.5vol%, or 3vol%, or 3.5vol%, or 4vol%, or 4.5vol%, or 5vol%, or 6vol%, or 7vol%, or 8vol%, or 9vol%, or 10vol%, or any intermediate value or range disclosed therein.
[0089] In some embodiments, a dry etching process is performed, which includes at least one of ion beam etching, plasma etching, reactive ion etching, or a combination thereof, using a suitable gas, such as oxygen-containing, nitrogen-containing, halogen-containing, or fluorine-containing, or a combination thereof.
[0090] In some embodiments, the etching process can be performed for a time in the range of 1 second to 24 hours, 5 seconds to 20 hours, 10 seconds to 16 hours, 20 seconds to 12 hours, 30 seconds to 8 hours, 45 seconds to 4 hours, or any intermediate value or range disclosed therein. In some examples, the etching process can be performed in a time range of 1 second to 300 seconds, or 5 seconds to 250 seconds, or 10 seconds to 200 seconds, or 20 seconds to 150 seconds, or 10 seconds to 120 seconds, or 20 seconds to 120 seconds, or 30 seconds to 120 seconds, or 45 seconds to 120 seconds, or 60 seconds to 120 seconds, or 90 seconds to 120 seconds, or any intermediate value or range disclosed therein. In some examples, the etching process can be performed for 1 second, or 5 seconds, or 10 seconds, or 20 seconds, or 30 seconds, or 45 seconds, or 60 seconds, or 75 seconds, or 90 seconds, or 105 seconds, or 120 seconds, or 150 seconds, or 180 seconds, or 210 seconds, or 240 seconds, or 270 seconds, or 300 seconds, 4 hours, or 8 hours, or 12 hours, or 16 hours, or 20 hours, or 24 hours, or any intermediate value or range disclosed therein.
[0091] In some embodiments, the selection of any etchant is independent of any time or time range and concentration or concentration range. For example, the etching process can be performed as a wet chemical etch using 0.5 vol% HF, etc.
[0092] Thus, in step 3, after simultaneous forming and phase separation, the glass sample is etched to form a porous surface structure whose channel width is determined by the size of the silica-poor phase region and the heat treatment conditions. In other words, the etching process produces a graded glass refractive index level greater than 5 nm (e.g., 50 nm) or 1 nm to 100 nm, or 100 nm to 1 micron, or 1 micron to 5 microns by removing boron or other elements near the cladding glass / air interface.
[0093] By etching treatment as described herein, the boron-rich phase is removed. Therefore, as long as phase separation produces two phases, and one of them is preferentially etched at a higher or lower rate, the etching treatment can be preferentially directed to the specific elements of the coating composition. However, the preferential etching depends on the glass. For example, in borosilicate glass, the etching rate of the boron matrix is usually faster than that of the silicate matrix. In other systems (e.g., aluminosilicate glass) that do not contain boron, phase separation may occur due to its unique chemical properties.
[0094] By controlling the heat treatment that causes phase separation and the etching treatment that removes the second phase from the discrete dispersed regions, the average pore size and porosity of the porous region can be changed. In addition, the use of strong etchants or long etching times may also slightly increase the pore size. In embodiments, the average pore size and porosity of the porous region can affect the light reflection and refraction of the shaped glass laminated article, thereby providing an anti-reflection and / or refraction effect on the shaped glass laminated article. In addition, controlling the thickness of the porous region in the laminated glass article, such as by controlling the heat treatment and etching treatment as described above, can result in a reduction in reflectivity at visible and IR wavelengths.
[0095] The porous regions described herein have anti-reflective properties that are partially affected by the average pore size of the porous region. Thus, in some embodiments, the average pore size of the porous region is greater than or equal to 10 nm and less than or equal to 200 nm, such as greater than or equal to 25 nm and less than or equal to 200 nm, greater than or equal to 50 nm and less than or equal to 200 nm, greater than or equal to 75 nm and less than or equal to 200 nm, greater than or equal to 100 nm and less than or equal to 200 nm, greater than or equal to 125 nm and less than or equal to 200 nm, greater than or equal to 150 nm and less than or equal to 200 nm, greater than or equal to 175 nm and less than or equal to 200 nm, greater than or equal to 200 nm, or greater than or equal to 200 nm. 10 nm or more and 175 nm or less, 25 nm or more and 175 nm or less, 50 nm or more and 175 nm or less, 75 nm or more and 175 nm or less, 100 nm or more and 175 nm or less, 125 nm or more and 175 nm or less, 150 nm or more and 175 nm or less, 10 nm or more and 150 nm or less, 25 nm or more and 175 nm or less, 150 nm or more and 175 nm or less, 10 nm or more and 150 nm or less, 25 nm or more and 175 nm or less, 10 nm or more and 175 nm or less, 125 nm or more and 175 nm or less, 150 nm or more and 175 nm or less, 10 nm or more and 150 nm or less, 25 nm or more and 175 nm or less, 150 nm or more and 175 nm or less 50 nm and less than or equal to 150 nm, 75 nm and less than or equal to 150 nm, 100 nm and less than or equal to 150 nm, 125 nm and less than or equal to 150 nm, 10 nm and less than or equal to 125 nm, 25 nm and less than or equal to 125 nm, 50 nm and less than or equal to 125 nm, 75 nm and less than or equal to 125 nm, 100 nm and less than or equal to 125 nm, 10 nm and less than or equal to 125 nm, m and less than or equal to 100nm, greater than or equal to 25nm and less than or equal to 100nm, greater than or equal to 50nm and less than or equal to 100nm, greater than or equal to 75nm and less than or equal to 100nm, greater than or equal to 10nm and less than or equal to 75nm, greater than or equal to 25nm and less than or equal to 75nm, greater than or equal to 50nm and less than or equal to 75nm, greater than or equal to 10nm and less than or equal to 50nm, greater than or equal to 25nm and less than or equal to 50nm, or greater than or equal to 10nm and less than or equal to 25nm.
[0096] In some embodiments, the porous region comprises a thickness of greater than or equal to about 50 nm and less than or equal to about 450 nm. In some embodiments, a porous region having a thickness of greater than or equal to 350 nm and less than or equal to 450 nm exhibits the reflective effects described above, such as a porous region having a thickness of greater than or equal to 360 nm and less than or equal to 450 nm, greater than or equal to 370 nm and less than or equal to 450 nm, greater than or equal to 380 nm and less than or equal to 450 nm, greater than or equal to 390 nm and less than or equal to 450 nm, greater than or equal to 400 nm and less than or equal to 450 nm, greater than or equal to 410 nm and less than or equal to 450 nm, greater than or equal to 420 nm and less than or equal to 450 nm, greater than or equal to 430 nm and less than or equal to 440 nm. In some embodiments, the porous region comprises a thickness of greater than or equal to 200 nm and less than or equal to 350 nm, ... In some embodiments, the porous region comprises a thickness greater than or equal to about 50 nm and less than or equal to about 180 nm, for example, a thickness ranging from 129.5-156.3 nm, 134.0-136.2 nm, or 96.25-125.1.
[0097] Figure 7 A graph 420 illustrating the transmittance at different wavelengths of glass articles formed by various methods is shown. Line 422 represents a control sample (i.e., glass article 100) obtained from a melt draw. Line 424 represents a sample that was heat treated in a conventional box or lehr, then etched, but not yet formed. Line 426 represents a sample that was simultaneously heat treated and formed in a hot press, as described in the present disclosure, and etched. Line 428 represents a sample that was heat treated in a box or lehr, then formed in a hot press, and finally etched.
[0098] Figure 8A graph 430 illustrating the reflectivity at different wavelengths of glass articles formed by various methods is shown. Line 432 represents a control sample (i.e., glass article 100) obtained from a melt draw. Line 434 represents a sample that was heat treated in a conventional box or lehr, then etched, but not yet formed. Line 436 represents a sample that was simultaneously heat treated and formed in a hot press, as described in the present disclosure, and etched. Line 438 represents a sample that was heat treated in a box or lehr, then formed in a hot press, and finally etched.
[0099] It should be understood that Figure 7-8 The measurements in are taken from the center of each sample. The average transmittance of the sample prepared according to the method of the present disclosure (i.e., simultaneous 3D thermoforming and phase separation of the glass article) shown by line 426 is greater than 98%, which is only slightly lower than the unformed treated reference sample shown by line 424. The average reflectance of the sample prepared according to the method of the present disclosure (i.e., simultaneous 3D thermoforming and phase separation of the glass article) shown by line 426 is less than 1%, which is similar to the unformed treated reference sample shown by line 424.
[0100] Fig. 9 1 is a perspective view of a glass article 120, which, as previously described, is formed by the method of the present disclosure. Measurements are taken at reference points L, T, C, B, and R, as shown on the glass article 120, where C is the geometric centroid of the glass article 120. The distance between point C and point L is about 30 mm. The distance between point C and point R is about 30 mm. The distance between point C and point T is about 65 mm. The distance between point C and point B is about 65 mm. Fig.10 Shows Fig. 9 440 shows a graph of reflectivity at different wavelengths at different locations around the glass article 120. For example, line L represents the reflectivity at different wavelengths at location L of the glass article 120. Line T represents the reflectivity at different wavelengths at location T of the glass article 120. Line C represents the reflectivity at different wavelengths at location C of the glass article 120. Line B represents the reflectivity at different wavelengths at location B of the glass article 120. Line R represents the reflectivity at different wavelengths at location R of the glass article 120. As shown in the graph 440, the locations marked with C, R, and L are similar in terms of reflectivity measurements, while the locations marked with T and B have greater variation compared to the center of the glass article 120.
[0101] Fig.11 Shows Fig. 9Microstructure images captured using a scanning electron microscope (SEM) at various locations around the glass article 120 are shown. Image 450 shows region L having a surface treatment layer 452 of approximately 129.5-156.3 nm. Image 470 shows region C having a surface treatment layer 472 of approximately 134.0-136.2 nm. Image 490 shows region R having a surface treatment layer 492 of approximately 96.25-125.1 nm. Thus, regions C, R, and L have a surface treatment layer of approximately 125 nm. Assuming an average of 125 nm, the glass article 120 includes a percentage deviation of less than 12% between regions C, R, and L, for example, approximately 11.31%, where the percentage deviation is calculated using the following steps: 1) Calculate the deviation of each point according to the equation
[0102]
[0103] Where D is the average deviation, d is the value of the data point, m is the mean (e.g., 125 nm), and || represents the absolute value; 2) calculate the average of the deviations calculated in step 1); 3) divide the average calculated in step 2) by the mean (e.g., 125 nm) and multiply by 100.
[0104] Fig.12 Show description Fig. 9 Warp measurement surface map 500 of glass article 120 is shown. The central region of glass article 120 is intended to be flat. To check flatness after the simultaneous 3D thermoforming and phase separation steps, the warp of the concave surface of the central region was measured with a parameter of 7.5 mm inside all edges and a spacing of 5 mm between each measurement. Due to the nature of the gauge and the shape of the part, the opposite side of the glass article 120 could not be measured. The maximum warp value (i.e., the difference between the highest and lowest points on the surface) reported was 0.038 mm, which is considered to be a low maximum warp value and therefore a desirable result.
[0105] The present disclosure has been described in detail with reference to specific embodiments, but it should be understood that changes and modifications can be made within the spirit and scope of the present disclosure. Therefore, the embodiments of the present disclosure are considered to be illustrative in all aspects, rather than restrictive. The scope of the present disclosure is indicated by the appended claims, and all changes within the meaning and scope of its equivalents are intended to be included therein.
Claims
1. A method of forming a shaped glass laminate, comprising: preheating a substrate comprising a core layer and at least one cladding layer, the at least one cladding layer comprising a phase-separable glass composition; Simultaneously heat treating and thermoforming the substrate so that the at least one cladding layer phase separates and at least a portion of the substrate is deformed to form the shaped glass laminate, the simultaneous heat treating and thermoforming of the substrate comprising heating the substrate and simultaneously pressing the substrate; as well as The substrate is etched.
2. The method according to claim 1, wherein the step of simultaneously heat treating and thermoforming the substrate further comprises: The substrate is cooled.
3. The method according to any one of the preceding claims, wherein the step of preheating the substrate comprises: The substrate is heated to a temperature below the glass transition temperature of the at least one cladding layer.
4. The method according to any one of the preceding claims, wherein the step of preheating the substrate comprises heating the substrate using a plurality of preheating stages, each preheating stage comprising a preheating temperature range and a preheating hold time.
5. The method according to any one of the preceding claims, wherein the step of simultaneously heat treating and thermoforming the substrate comprises: heating the substrate to a temperature ranging from a glass transition temperature of the at least one cladding layer to a softening point of the at least one cladding layer; as well as A pressure of at least 0.9 MPa is applied to the substrate.
6. The method according to any one of the preceding claims, wherein the step of simultaneously heat treating and thermoforming the substrate comprises: The substrate is simultaneously heated to about 750° C. and a pressure of about 0.9 MPa is applied to the substrate for at least 600 seconds.
7. The method according to any one of the preceding claims, wherein the steps of simultaneously heat treating and thermoforming the substrate comprise: The substrate is simultaneously heated at about 750° C. and a pressure of about 0.9 MPa is applied to the substrate on a forming surface for at least 1200 seconds.
8. The method according to any one of claims 1 and 2, wherein the step of simultaneously heat treating and thermoforming the substrate comprises: The substrate is simultaneously heated at a temperature of greater than or equal to about 710° C. and contacted with a forming surface at a pressure in a range of 0.1 MPa to 0.9 MPa.
9. The method according to any one of claims 1 and 2, wherein the step of simultaneously heat treating and thermoforming the substrate comprises: The substrate is simultaneously heated to a temperature at which the at least one coating layer undergoes spinodal phase separation and is contacted with a forming surface under a pressure that causes deformation of the substrate.
10. The method of claim 9, wherein the forming surface comprises a pre-forming mold.
11. The method according to any one of claims 2 to 10, wherein the step of cooling the substrate comprises: The substrate is cooled using multiple cooling stages, each cooling stage comprising a cooling temperature range, pressure, and cooling hold time.
12. The method according to any one of the preceding claims, wherein the step of etching the substrate comprises: applying at least a 2 volume percent hydrogen fluoride (HF) solution to the substrate for at least 90 seconds; immersing the substrate in a dihydrogen monoxide (H2O) bath for at least 120 seconds; rinsing the substrate in deionized water; as well as The substrate was purged with nitrogen (N2).
13. A method of forming a phase separated glass laminate having improved anti-reflection (AR) and anti-glare (AG) properties, the method comprising: Providing a substrate, the substrate comprising a core layer and at least one cladding layer fused to the core layer; The substrate was simultaneously heat treated and formed using a heat press as follows: heating the substrate to a temperature at which the at least one coating layer undergoes spinodal phase separation; and pressing the substrate onto a forming surface; and The substrate is etched.
14. The method of claim 13, wherein the step of heating the substrate to a temperature at which the at least one coating layer undergoes spinodal phase separation comprises: The substrate is heated to a temperature ranging from a glass transition temperature of the at least one cladding layer to a softening point of the at least one cladding layer for at least 1200 seconds.
15. The method of any one of claims 13-14, wherein the step of pressing the substrate onto the forming surface comprises: placing the substrate on a preform mold; as well as A first pressure of at least 0.9 MPa is applied to the substrate for at least 1200 seconds.
16. The method according to claim 15, further comprising: The first pressure applied to the substrate is reduced from 0.9 MPa to a second pressure ranging from 0.1 MPa to 0.4 MPa.
17. The method according to any one of claims 13 to 16, further comprising, before the step of simultaneously heat treating and shaping the substrate: The substrate is preheated to a temperature below the glass transition temperature of the at least one cladding layer.
18. A method of forming and shaping a phase separated glass laminate having improved anti-reflection (AR) and anti-glare (AG) properties, comprising: providing a substrate including a core layer and at least one cladding layer; The substrate was simultaneously heat treated and formed using a heat press as follows: preheating the substrate to a first temperature; heating the substrate to a second temperature greater than the first temperature at which the at least one coating layer undergoes spinodal phase separation, while pressing the substrate into a forming surface at a first pressure to permanently deform the substrate; as well as cooling the substrate to a third temperature lower than the second temperature while pressing the substrate into the forming surface at a second pressure less than the first pressure; as well as The substrate is etched.
19. The method of claim 18, wherein the step of simultaneously heat treating and shaping the substrate further comprises: The substrate is cooled to a fourth temperature that is lower than the third temperature while being pressed into the forming surface at a third pressure that is less than the second pressure.
20. The method according to any one of claims 18-19, wherein: The second temperature is in the range of 710°C to 750°C; and The first pressure is greater than 0.4 MPa.
21. A shaped glass laminate article comprising: Core layer; at least one cladding layer fused to the core layer, the at least one cladding layer comprising a porous region on an outer surface thereof, the core layer and the at least one cladding layer being deformed to form the shaped glass laminate, wherein: The shaped glass laminate article has a transmittance greater than 98% across the entire spectrum from about 400 nm to about 2200 nm; and The shaped glass laminate article has a reflectivity at the outer surface of less than 1% over the entire spectral range from about 400 nm to 2200 nm.
22. The shaped glass laminate article of claim 21, wherein the porous region has an average pore size greater than or equal to 10 nm and less than or equal to 200 nm.
23. The shaped glass laminate article of any one of claims 21-22, wherein the porous region has an average pore size greater than or equal to 20 nm and less than or equal to 150 nm.
24. The shaped glass laminate article of any one of claims 21-23, wherein the porous region has a porosity greater than or equal to 0.16 and less than or equal to 0.
22.
25. The shaped glass laminate article of any one of claims 21-24, wherein the porous zone has a thickness greater than or equal to 350 nm and less than or equal to 450 nm.
26. The shaped glass laminate article of any one of claims 21-25, wherein the porous zone has a thickness greater than or equal to 375 nm and less than or equal to 400 nm.
27. The shaped glass laminate article of any one of claims 21-26, wherein the porous zone has a percent deviation in thickness of less than 12%.
28. A shaped glass laminate article comprising: Core layer; at least one cladding layer fused to the core layer, the at least one cladding layer comprising a porous region on an outer surface thereof, the core layer and the at least one cladding layer being deformed to form the shaped glass laminate, wherein: The shaped glass laminate article has a transmittance greater than or equal to 97% over the entire spectral range from about 400 nm to about 2200 nm; and The shaped glass laminate article has a reflectivity at the outer surface of less than or equal to 3% over the entire spectral range from about 400 nm to 2200 nm.
29. The shaped glass laminate article of claim 28, wherein the shaped glass laminate article has a transmittance greater than 98% across the entire visible spectrum from about 400 nm to about 2200 nm.
30. The shaped glass laminate article of any one of claims 28-29, wherein the shaped glass laminate article has a reflectivity of less than 1% across the visible spectrum from about 400 nm to about 2200 nm.
31. The shaped glass laminate article of any one of claims 28-30, wherein the porous region has an average pore size greater than or equal to 10 nm and less than or equal to 200 nm.
32. The shaped glass laminate article of any one of claims 28-31, wherein the porous region has a porosity greater than or equal to 0.16 and less than or equal to 0.
22.
33. The shaped glass laminate article of any one of claims 28-32, wherein the porous zone has a thickness greater than or equal to 350 nm and less than or equal to 450 nm.
34. The shaped glass laminate article of any one of claims 28-33, wherein the porous zone has a percent deviation in thickness of less than 12%.
Citation Information
Patent Citations
Forming laminated sheet glass
US4214886A